Intergroup relations and fundamental dimensions of social judgment. - Costa-Lopes, Rui Alberto Morais (2016)
The goal of this paper is to review the literature on the fundamental dimensions of social judgment and reflect on how these can help to boost our understanding of attitudes towards immigrants. We start by reviewing the work on the “fundamental dimensions” along which these judgments are organized, describing the different conceptions that have been put forward, identifying the regularities found in the content of these dimensions and the distinctions between them. Next, we propose a new way of looking at these fundamental dimensions by situating them within the specific field of intergroup relations in an immigration context, and explain how all the different examples of dimensions map onto this “new perspective”. We conclude by discussing how these two dimensions mirror the two fundamental topics that organize the discourse and the opinions about immigrants and immigration in society, and how attitudes towards immigrants can be differentially shaped by these two fundamental dimensions.